2015
DOI: 10.1093/infdis/jiv140
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Ebola Virus Entry Into Macrophages

Abstract: Ebolaviruses constitute a public health threat, particularly in Central and Western Africa. Host cell factors required for spread of ebolaviruses may serve as targets for antiviral intervention. Lectins, TAM receptor tyrosine kinases (Tyro3, Axl, Mer), T cell immunoglobulin and mucin domain (TIM) proteins, integrins, and Niemann-Pick C1 (NPC1) have been reported to promote entry of ebolaviruses into certain cellular systems. However, the factors used by ebolaviruses to invade macrophages, major viral targets, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 49 publications
3
49
0
1
Order By: Relevance
“…Consistent with this, it was shown that infection of bone marrow derived dendritic cells with several enveloped viruses, including EBOV, was significantly enhanced by TAM‐mediated inhibition of TLR and IFN signaling . It is reasonable to postulate that TAM signaling in macrophages may play an important, yet currently poorly appreciated, role in EBOV pathogenesis because macrophages up‐regulate Mer expression during maturation, EBOV uses Mer for entry into macrophages, and SOCS1 and SOCS3 are increased upon infection of macrophages with EBOV . In addition, the production of SOC3 through signaling pathways activated by TAM receptors has been shown to lead to enhanced EBOV budding, providing an additional mechanism by which virus production may be increased.…”
Section: Ebov Elicits Mϕ Immunopathologymentioning
confidence: 76%
See 2 more Smart Citations
“…Consistent with this, it was shown that infection of bone marrow derived dendritic cells with several enveloped viruses, including EBOV, was significantly enhanced by TAM‐mediated inhibition of TLR and IFN signaling . It is reasonable to postulate that TAM signaling in macrophages may play an important, yet currently poorly appreciated, role in EBOV pathogenesis because macrophages up‐regulate Mer expression during maturation, EBOV uses Mer for entry into macrophages, and SOCS1 and SOCS3 are increased upon infection of macrophages with EBOV . In addition, the production of SOC3 through signaling pathways activated by TAM receptors has been shown to lead to enhanced EBOV budding, providing an additional mechanism by which virus production may be increased.…”
Section: Ebov Elicits Mϕ Immunopathologymentioning
confidence: 76%
“…EBOV enters cells through a complex series of steps that can be broken down into relatively non‐specific extracellular, and highly specific intracellular events. EBOV initially binds to the surface of host cells by engaging either C‐type lectins (CLECs), which bind to N‐ or O‐linked glycans on the heavily glycosylated Ebola glycoprotein, or phosphatidylserine (PS) receptors which mediate clearance of apoptotic bodies . In the context of enveloped virus infections, PS receptors recognize PS in the host‐derived outer membrane of the virion.…”
Section: Receptors On Dcs Monocytes and Mϕ And Filovirus Entry And mentioning
confidence: 99%
See 1 more Smart Citation
“…Macrophages and dendritic cells (DCs) are early targets in EBOV pathogenesis. Once infected, these cells gain access to the blood and disseminate the virus systemically into tissues and blood vasculature [10][11][12]16]. Viral invasion of endothelia and production of pro-inflammatory cytokines by the circulating infected macrophages and DCs lead to the development of viral hemorrhagic fever that is characteristic of EBOV infection [13].…”
Section: Introductionmentioning
confidence: 99%
“…Ebola GP expression also led to the down regulation of integrins [12]. Integrand αV was required for efficient GP-mediated transduction and EBOV infection of macrophages [13]. Binding of Ebola virus GP to aVbIII integrins is also shown to prime the endosomal cathepsins, a necessary step in the Ebola virus entry [14].…”
mentioning
confidence: 99%